Musical intelligence among the students of the fourth preparatory class (Journal of the College of Basic Education, 2022)
The current research aims to identify the extent to which the fourth preparatory grade students possess musical intelligence and is there a difference between them in intelligence according to specialization (scientific - literary) and gender (male - female).